ANALISIS ASAS HUKUM ULTIMUM REMEDIUM DALAM TINDAK PIDANA PERPAJAKAN DI INDONESIA: Analysis of the Legal Principle of Ultimum Remedium in Tax Crime in Indonesia - Kurniawan, Deny (Jurnal Globalisasi Hukum., 2024)
The principle of ultimum remedium in tax crimes in Indonesia is a principle in Indonesian criminal law stating that criminal law should be used as a last resort in law enforcement. This paper discusses tax crimes as criminal acts within the scope of administrative law (administrative criminal law or dependent crimes), where the aim of law enforcement is to ensure taxpayers fulfill their tax obligations, namely reporting and paying taxes. Criminal sanctions in the general tax provisions law should be understood differently from the main objective of tax law, which is to secure state revenue from the tax sector. Therefore, criminal sanctions in tax law can serve as a last resort to provide a deterrent effect in the law enforcement process (ultimum remedium).